The Influence of Carbonization Temperature Variations on the Quality of Durian Peel-Based Bio-briquettes - Nury, Dennis; Luthfi, Muhammad Zulfikar; Saputra, Andri (Journal of Chemical Process Engineering, 2024)
The increasing global energy demand and environmental concerns necessitate the development of alternative energy sources. Durian peel, an abundant agricultural waste in Indonesia, presents significant potential for bio-briquette production due to its high cellulose and lignin content. This study investigates the effect of carbonization temperature on the quality of durian peel-based bio-briquettes. Carbonization was conducted at 300°C, 400°C, 500°C, and 600°C, with proximate analysis and calorific value determination performed according to SNI 01-6235-2000 standards. The results demonstrate that higher carbonization temperatures reduce moisture and volatile matter while increasing fixed carbon and calorific value. At 500°C, the bio-briquettes exhibited optimal properties, including moisture content (7.47%), volatile matter (13.54%), and a calorific value exceeding 5000 cal/g, meeting the SNI standard. However, ash content at this temperature (9.33%) slightly exceeded the standard (≤8%), highlighting a trade-off between energy efficiency and residual minerals. This study concludes that 500°C is the optimal carbonization temperature for producing high-quality bio-briquettes from durian peel, balancing energy output and combustion efficiency. Further optimization of the process is recommended to enhance fixed carbon content and minimize ash. These findings contribute to sustainable energy practices by transforming agricultural waste into a renewable energy resource, addressing both waste management and energy challenges.